Degloving Injury of Bowel: An Unheard Complication of Surgical Abortion - Chawla, Sonia (J Clin Diagn Res, 2016)
Unsafe abortion is one of the leading causes of maternal mortality. Various types of intestinal injury in form of haematoma, perforation, contusion and transection have been reported. Degloving injury of intestine is one of the rarest complications. We report a case of 32-year-old lady Gravida 4, para 3 admitted with history of induced surgical abortion by a quack with degloving injury to bowel. Though there was no fecal soiling of peritoneal cavity but large segment of bowel was lost. She was managed by end ileostomy and discharged in stable condition.